“Sri Lankan research output at international level - A Picture from Scopus” - Navaneethakrishnan, S. (Faculty of Social Sciences, University of Kelaniya, 2013)
Abstract Highlighting the various output patterns of research publications of Sri lanka, present study identified the trends in Sri Lankan research performance as reflected by the research publications output between years 1980 -2009 based on scientific publications included in the SciVerse Scopus database. The objective of the study was to identify the research trends in Sri Lankan research performance as reflected by the research publications output during the study period and to identify the contribution of Sri Lanka in global research output. Quantitative methodological approach was taken, based on bibliometric analysis. The process of article selection was as follows: Affiliation - 'Sri Lanka' or ‘Srilanka’ or 'Ceylon', Publication year - 'January 1980 to December 2010'. Results of this study show globally, 8,694 papers were published during the study period, including 11 document types. Among them, there were 6,671 articles. Research publications of Sri Lanka were rise up significantly in the past three decades and the highest number of researches was published in year 2010. The most preferred language by scientist is English with 8,647 publications. The most productive authors are Tennakone, K., Ratnasooriya, W.D. and De Silva H.J. It was found that the University of Peradeniya leads other institutions in linear growth of output followed by University of Colombo and University of Kelaniya. The output of Medicine was found to be larger than other subjects, which was followed by Agricultural and Biological sciences and engineering and environmental sciences. Ceylon Medical Journal at the first rank of journal title for Scientists to publish their research findings followed by Journal of the National Science Foundation of Sri Lanka. The suggestion of this research is to setup an enabling environment for researchers to publish their research findings at international level and collaborations across the nations need to be encouraged among the researchers. (298words)
Keywords: Bibliometrics; Scholarly communication; Sri Lanka